Nasal cavity hemostatic sponge and preparation method thereof
By using amino alcohol and hydrazide graft modified oxidized hyaluronate and gelatin, a hydrogel hemostatic sponge with polycalcium phosphate particles is formed, which solves the secondary injury problems caused by the existing nasal hemostatic materials after removal, and achieves efficient hemostatic and good healing effects.
Patent Information
- Application Number
- CN202510048538.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-22
AI Technical Summary
The existing nasal hemostasis materials are often accompanied by secondary injury after removal, and the nasal mucosa adheres and scab rupture, resulting in secondary damage, and their mechanical properties, adhesion properties and biodegradability after absorption are defective.
The hydrogel was formed by mixing and reactions by using amino alcohol graft-modified oxidized hyaluronate and hydrazide graft-modified gelatin, and a hemostatic sponge was obtained by cryogenic freezing. This method generates polycalcium phosphate particles in situ, enhancing hemostatic properties and mechanical properties.
It achieves effective hemostasis effect, has excellent wet adhesion properties, mechanical properties and biocompatibility, has high compressive strength after fluid absorption, and has high cell survival rate, which can effectively promote wound healing.
Smart Images

Figure BDA0005239268880000071 
Figure BDA0005239268880000091 
Figure BDA0005239268880000121
Abstract
Description
Technical Field
[0001] The invention relates to the field of biomedical materials, and in particular to a nasal hemostatic sponge and a preparation method thereof. Background Art
[0002] According to statistics, there are more than 30 million cases of chronic sinusitis diagnosed worldwide each year. Among them, functional endoscopic sinus surgery is often used to treat patients with chronic sinusitis in clinical practice. However, postoperative complications such as postoperative bleeding, scar tissue, adhesions, and poor wound healing often lead to insufficient improvement of postoperative symptoms and the need for secondary surgery. In this case, traditional non-absorbable packings are used to achieve postoperative hemostasis. There are many varieties of commercial sponge materials used in clinical practice, and the effects of use vary, but they often lead to adhesion of the nasal mucosa and foreign body reaction. In general, high-quality hemostatic materials should have the following characteristics: 1) apply pressure to help stop bleeding; 2) fill the nasal cavity to provide support; 3) balance moisture to prevent excessive evaporation of water vapor and promote wound healing; 4) establish a barrier to prevent mucosal adhesion; 5) be degradable to gradually reduce the applied pressure for easy removal. Commercial hemostatic materials, including vaseline gauze and PVA medical sponges, are often used to solve the problem of hemostasis after sinusitis surgery. However, these two typical materials are insoluble and removal is often accompanied by secondary injury, adhesion to the nasal mucosa and rupture of the crust, leading to secondary injury.
[0003] Based on this, researchers have used a variety of natural polymers to give nasal hemostatic materials procoagulant properties, such as chitosan, gelatin, collagen, alginate and cellulose. Gelatin sponge has obvious hemostatic effect when used for nasal bleeding. Gelatin is a product of collagen hydrolysis, with high biocompatibility and degradability, avoiding secondary damage to patients when removed. However, the mechanical properties of gelatin sponge are not satisfactory during application. Chitosan hemostatic sponge also has the characteristics of water absorption and swelling, which can absorb exuded tissue fluid in time when it comes into contact with the wound surface. Not only that, the polycation of chitosan can activate platelets and activate thrombin, and has a good hemostatic effect. In recent years, alginate, polylactic acid and cellulose sponges reported in recent years have a wide range of application scenarios and excellent effects, but when used for nasal hemostasis, their mechanical properties, adhesion properties and biodegradability after absorbing fluid have certain defects.
[0004] Therefore, the development of a hemostatic sponge with strong hemostatic ability, good biocompatibility, good air permeability and mechanical properties that meet the requirements is an inevitable demand in the field of postoperative hemostasis for sinusitis. Summary of the invention
[0005] In view of this, the present invention provides a nasal hemostatic sponge and a preparation method thereof. The nasal hemostatic sponge prepared by the present invention can effectively stop bleeding and has excellent wet adhesion performance, mechanical properties, and biocompatibility.
[0006] The present invention provides a method for preparing a nasal hemostatic sponge, comprising the following steps:
[0007] A): mixing the amino alcohol graft-modified oxidized hyaluronate, a buffer solution and a calcium ion donor to obtain a first solution;
[0008] B): mixing the hydrazide grafted modified gelatin, a buffer solution and a polyphosphate solution to obtain a second solution;
[0009] C): mixing the first solution and the second solution to obtain a hydrogel; then freezing the hydrogel to obtain a hemostatic sponge;
[0010] There is no order restriction for step A) and step B).
[0011] Preferably, the amino alcohol grafted modified oxidized hyaluronate is prepared by the following preparation method:
[0012] S1: dissolving oxidized hyaluronate in a solvent to obtain an oxidized hyaluronate solution;
[0013] S2: mixing the oxidized hyaluronate solution with amino alcohol and an activator to react to form amino alcohol grafted modified oxidized hyaluronate;
[0014] The hydrazide grafted modified gelatin is prepared by the following preparation method:
[0015] K1: dissolving gelatin in a solvent to obtain a gelatin solution;
[0016] K2: The gelatin solution is mixed with hydrazide, heated to dissolve, and then an activator is added to react to form hydrazide grafted modified gelatin.
[0017] Preferably, the amino alcohol used to form the amino alcohol-grafted modified oxidized hyaluronate is at least one of 4-amino-1-butanol, 5-amino-1-pentanol, 6-amino-1-hexanol and 7-amino-1-heptanol;
[0018] The oxidized hyaluronate used to form the amino alcohol graft-modified oxidized hyaluronate is an oxidized hyaluronate; wherein the hyaluronate is sodium hyaluronate;
[0019] The hydrazide grafted modified gelatin is adipic acid dihydrazide grafted modified gelatin;
[0020] The gelatin used to form the hydrazide grafted modified gelatin is type A gelatin;
[0021] The calcium ion donor is an inorganic salt containing calcium;
[0022] The polyphosphate solution is a sodium polyphosphate solution.
[0023] Preferably, the calcium ion donor is at least one of calcium sulfate, calcium chloride and calcium lactate;
[0024] The polyphosphate solution is at least one of a sodium hexametaphosphate solution and a sodium tripolyphosphate solution.
[0025] Preferably, the degree of oxidation of the amino alcohol graft-modified oxidized hyaluronate is 11% to 86%;
[0026] The grafting rate of the amino alcohol graft-modified oxidized hyaluronate is 9% to 62%;
[0027] The grafting rate of the hydrazide grafted modified gelatin is 37% to 65%.
[0028] Preferably, the concentration of the amino alcohol grafted modified oxidized hyaluronate in the first solution is 2 wt% to 6 wt%, and the concentration of the calcium ion donor is 1.0 wt% to 1.4 wt%;
[0029] The concentration of hydrazide-grafted modified gelatin in the second solution is 5wt% to 15wt%, and the concentration of polyphosphate is 0.6wt% to 1.0wt%; the concentration of the polyphosphate solution used is 0.1 to 0.3 mol / L;
[0030] The mass ratio of the first solution to the second solution is 1:(1-1.5).
[0031] Preferably, the oxidized hyaluronate used to form the amino alcohol grafted modified oxidized hyaluronate is prepared by the following preparation method: hyaluronate reacts with sodium periodate to form oxidized hyaluronate.
[0032] Preferably, the preparation method of the oxidized hyaluronate specifically comprises:
[0033] H1: dissolving hyaluronate in a solvent to obtain a hyaluronate solution;
[0034] H2: dissolving sodium periodate in a solvent to obtain a sodium periodate solution;
[0035] H3: adding the sodium periodate solution dropwise to the hyaluronate solution, reacting in the dark to form oxidized hyaluronate;
[0036] There is no order restriction for step H1 and step H2.
[0037] Preferably, the hyaluronate is replaced with alginate, sodium carboxymethylcellulose or chondroitin sulfate;
[0038] and / or
[0039] The gelatin therein is replaced with other collagen hydrolysates or polymers.
[0040] The present invention also provides a nasal hemostatic sponge, which is prepared by the preparation method described in the above technical solution.
[0041] The preparation method provided by the present invention comprises the following steps: using amino alcohol to graft-modify hyaluronic acid, and using hydrazide to modify gelatin; dissolving the amino alcohol graft-modified oxidized hyaluronate in a buffer solution, adding a calcium ion donor to form a first solution; dissolving the hydrazide-modified gelatin in a buffer solution, and adding polyphosphate to form a second solution; mixing the first solution and the second solution to react to form a hydrogel, and the formed hydrogel is subjected to a low-temperature freezing gel process to obtain a hemostatic sponge. The hemostatic sponge of the present invention can generate polycalcium phosphate particles in situ while cross-linking, can effectively stop bleeding, has low processing cost, can be used in a wide range, has good wet adhesion performance, excellent mechanical properties, and good biocompatibility.
[0042] The test results show that the hemostatic sponge prepared by the present invention achieves the following effects: the hemolysis rate is below 0.4%, showing excellent blood compatibility; it has a rich porous structure and a high cross-linking density. The rich porous structure and the strong covalent bonds and interaction forces make the hemostatic sponge highly elastic and absorbent, and can be filled into the nasal cavity to achieve a rapid hemostatic effect and promote wound healing; the compressive strength after absorbing liquid is above 0.53MPa, and it has excellent strength under stress; the cell survival rate is above 95%, showing excellent cell compatibility; the wet surface firmness reaches above 4.9KPa, showing excellent wet environment adhesion; the liver bleeding repair test shows that it can effectively improve the hemostatic healing ability. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0044] Figure 1 FTIR images of sodium hyaluronate before and after being grafted with 4-amino-1-butanol;
[0045] Figure 2 1HNMR graphs of sodium hyaluronate before and after being grafted with 4-amino-1-butanol;
[0046] Figure 3 FTIR images of gelatin before and after being grafted with adipic acid dihydrazide;
[0047] Figure 41HNMR graphs of gelatin before and after it was grafted with adipic acid dihydrazide;
[0048] Figure 5 The hemolysis rate effect diagram of the sponges obtained in Example 3 and Comparative Examples 1-2;
[0049] Figure 6 The SEM images of the sponges obtained in Example 3 and Comparative Examples 1-2 are shown in FIG. Figure 6 (a) is the SEM image of the GO sponge obtained in Comparative Example 1, Figure 6 (b) is the SEM image of the GO-OH sponge obtained in Comparative Example 2. Figure 6 (c) is the SEM image of the GO-OH-CaP sponge obtained in Example 3;
[0050] Figure 7 The cell proliferation diagram of the sponges obtained in Example 3 and Comparative Examples 1-2;
[0051] Figure 8 The cell fluorescence live-dead staining images of the sponges obtained in Example 3 and Comparative Examples 1-2;
[0052] Fig. 9 Schematic diagram of the repair of mouse liver hemorrhage using the sponges obtained in Example 3 and Comparative Examples 1-2. DETAILED DESCRIPTION
[0053] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0054] In this article, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0055] As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items.
[0056] Herein, when it comes to numerical ranges, unless otherwise specified, the numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0057] In this article, when referring to the unit of a data range, if there is a unit only after the right endpoint, it means that the units of the left and right endpoints are the same. For example, 30~50min means that the units of the left endpoint "30" and the right endpoint "50" are both min.
[0058] Explanation of terms in this invention:
[0059] The "grafting modification" mentioned in the present invention is a modification method of introducing polar or functional side groups into the polymer macromolecular chain by chemical reaction.
[0060] The "in-situ formation" mentioned in the present invention means that the material is formed at the required position at one time with the required properties, including chemical composition, microstructure and function.
[0061] The present invention provides a method for preparing a nasal hemostatic sponge, comprising the following steps:
[0062] A): mixing the amino alcohol graft-modified oxidized hyaluronate, a buffer solution and a calcium ion donor to obtain a first solution;
[0063] B): mixing the hydrazide grafted modified gelatin, a buffer solution and a polyphosphate solution to obtain a second solution;
[0064] C): mixing the first solution and the second solution to obtain a hydrogel; then freezing the hydrogel to obtain a hemostatic sponge;
[0065] There is no order restriction for step A) and step B).
[0066] About Step A :
[0067] A): The amino alcohol graft-modified oxidized hyaluronate, a buffer solution and a calcium ion donor are mixed to obtain a first solution.
[0068] [About amino alcohol grafted modified oxidized hyaluronate]:
[0069] In the present invention, the amino alcohol grafted modified oxidized hyaluronate is a grafted modified product obtained by grafting oxidized hyaluronate with amino alcohol (ie, introducing amino alcohol side groups into the oxidized hyaluronate polymer chain).
[0070] About amino alcohols:
[0071] In the present invention, the amino alcohol is a small molecule with an amino group and a hydroxyl group at both ends of the alkyl chain, preferably at least one of 4-amino-1-butanol, 5-amino-1-pentanol, 6-amino-1-hexanol and 7-amino-1-heptanol, and more preferably 4-amino-1-butanol. The present invention has no particular restrictions on the source of the amino alcohol, which can be a commercial product or prepared according to a conventional preparation method in the art.
[0072] About Oxidized Hyaluronate:
[0073] In the present invention, the oxidized hyaluronate is an oxidized hyaluronate. The hyaluronate is preferably sodium hyaluronate. The present invention has no particular restrictions on the source of the hyaluronate, and it can be a commercial product.
[0074] In the present invention, the oxidized hyaluronate is preferably prepared by the following preparation method: hyaluronate reacts with sodium periodate to form oxidized hyaluronate.
[0075] In the present invention, the preparation method of the oxidized hyaluronate preferably comprises:
[0076] H1: dissolving hyaluronate in a solvent to obtain a hyaluronate solution;
[0077] H2: dissolving sodium periodate in a solvent to obtain a sodium periodate solution;
[0078] H3: adding the sodium periodate solution dropwise to the hyaluronate solution, reacting in the dark to form oxidized hyaluronate;
[0079] There is no order restriction for step H1 and step H2.
[0080] Regarding step H1: the hyaluronate is preferably sodium hyaluronate (HA). The solvent is preferably water, more preferably deionized water. The usage ratio of the hyaluronate to the solvent is preferably 2g: (100-250) mL, specifically 2g: 100 mL, 2g: 150 mL, 2g: 200 mL, 2g: 250 mL.
[0081] Regarding step H2: the solvent is preferably water, more preferably deionized water. The ratio of sodium periodate to solvent is preferably 1.072 g: (4-10) mL, specifically 1.072 g: 4 mL, 1.072 g: 5 mL, 1.072 g: 6 mL, 1.072 g: 7 mL, 1.072 g: 8 mL, 1.072 g: 9 mL, 1.072 g: 10 mL.
[0082] Regarding step H3: slowly drip sodium periodate solution into the hyaluronate solution, stir magnetically and avoid light to react. Wherein, the molar ratio of hyaluronate to sodium periodate is preferably 1: (0.3-2), specifically 1: 0.3, 1: 0.5, 1: 1.0, 1: 1.5, 1: 2.0. In the present invention, the molar number of the hyaluronate is calculated by the ratio of the total mass of hyaluronate / the number average molecular weight of hyaluronate. In the process of slowly dripping sodium periodate solution into the hyaluronate solution, magnetic stirring is accompanied and light is avoided. After the addition is completed, continue stirring and avoid light to react. The temperature of the reaction is not particularly limited, and it can be carried out at room temperature; herein, the room temperature can be 20-25°C, specifically 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, and the same applies to the following text. The time of the light-avoiding reaction is preferably 4-8h, specifically 4h, 5h, 6h, 7h, 8h. After the reaction is completed, ethylene glycol is preferably added to quench the unreacted oxidant to terminate the oxidation reaction. The molar ratio of ethylene glycol to hyaluronate is preferably (4-11):1, specifically 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1. After adding ethylene glycol, the reaction is carried out for 0.5-2h, specifically 0.5h, 1h, 2h. In the present invention, after the above reaction, oxidized hyaluronate is generated in the system to obtain a reaction solution containing oxidized hyaluronate. In the present invention, the above reaction solution is preferably post-treated to obtain oxidized hyaluronate. In the present invention, the post-treatment preferably includes: dialysis and freeze-drying. Among them, the dialysis bag used for dialysis is preferably a dialysis bag with a molecular weight cutoff of 8-1.4kDa; specifically, the obtained reaction solution is transferred to a dialysis bag, placed in deionized water for dialysis, and dialyzed for 3 days, and the dialysis solution is replaced every 8h. After dialysis, the solution in the dialysis bag is lyophilized, preferably for 3 days, to obtain oxidized hyaluronate solid.
[0083] In one embodiment, sodium hyaluronate is reacted with sodium periodate to prepare oxidized sodium hyaluronate, and the reaction scheme is as follows:
[0084]
[0085] In the present invention, the oxidation degree of the oxidized hyaluronate is preferably 11% to 86%. The oxidation degree refers to the molar percentage of the oxidized repeating units to all repeating units.
[0086] Regarding the grafting modification of oxidized hyaluronate with amino alcohols:
[0087] In the present invention, preferably, the amino alcohol grafted modified oxidized hyaluronate is prepared by the following preparation method:
[0088] S1: dissolving oxidized hyaluronate in a solvent to obtain an oxidized hyaluronate solution;
[0089] S2: mixing the oxidized hyaluronate solution with amino alcohol and an activator to react to form amino alcohol grafted modified oxidized hyaluronate.
[0090] Regarding step S1:
[0091] The solvent is preferably at least one of a PBS solution, an MES solution and water; wherein the water is preferably deionized water. The oxidized hyaluronate is dissolved in the solvent to obtain a uniform oxidized hyaluronate solution. The mass fraction of the oxidized hyaluronate in the oxidized hyaluronate solution is preferably 1wt% to 3wt%, specifically 1wt%, 2wt%, or 3wt%.
[0092] Regarding step S2:
[0093] Step S2 preferably specifically includes: S2a: dropping amino alcohol into the oxidized hyaluronate solution, mixing evenly, and obtaining a mixed solution; S2b: adding an activator to the mixed solution for reaction, maintaining the pH value at 4.5-5.5 during the reaction, and obtaining a reaction solution after the reaction is completed; S2c: dialyzing the reaction solution, freeze-drying, and obtaining an amino alcohol-grafted modified oxidized hyaluronate.
[0094] Wherein, the ratio of the molar number of repeating units in the oxidized hyaluronate to the molar number of amino alcohol is preferably 1: (0.5-30), specifically 1: 0.5, 1: 1, 1: 5, 1: 10, 1: 15, 1: 20, 1: 25, 1: 30. The activator is preferably EDCI (i.e. 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide) and NHS (i.e. N-hydroxysuccinimide). Wherein, the molar ratio of EDCI to NHS is preferably 1: (1-2), specifically 1: 1, 1: 1.5, 1: 2. The activator is preferably added in the form of a solution, that is, the activator is preliminarily dissolved in a solvent to form an activator solution, and then the activator solution is added into the system. The solvent is preferably DMSO (i.e. dimethyl sulfoxide) and water; wherein, the volume ratio of DMSO to water is preferably 1: 1. The mass fraction of the activator solution is preferably 8wt% to 16wt%, specifically 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%. The molar ratio of the oxidized hyaluronate to the activator is preferably 1: (2-3), specifically 1: 2, 1: 2.5, 1: 3. The temperature of the reaction is not particularly limited and can be carried out at room temperature. The reaction time is preferably 3 to 8h, more preferably 4 to 8h. The pH value is maintained at 4.5 to 5.5 during the reaction, and the maintenance method is preferably as follows: after adding the activator, add acid solution to adjust the pH value to 4.5 to 5.5, and continue to add acid solution during the reaction to maintain the pH value; preferably, the pH value is adjusted once every 3h, and preferably the pH value is maintained for more than 4h. The pH value can be specifically 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5. The acid solution is preferably an HCl solution. After the reaction at room temperature is completed, an amino alcohol grafted modified oxidized hyaluronate is generated in the system, and a reaction solution containing an amino alcohol grafted modified oxidized hyaluronate is obtained. The above reaction solution is dialyzed; specifically, the reaction solution is transferred to a dialysis bag and dialyzed in deionized water. The cutoff of the dialysis bag used for the dialysis is preferably 7 to 14 kDa, specifically 7 kDa, 8 kDa, 9 kDa, 10 kDa, 11 kDa, 12 kDa, 13 kDa, 14 kDa. The dialysis time is preferably 3 to 5 days, specifically 3 days, 4 days, and 5 days. In the dialysis ancient city, the dialysis solution is preferably replaced every 8 to 16 hours, specifically 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, and 16 hours. After dialysis, the solution in the dialysis bag is freeze-dried to obtain an amino alcohol grafted modified oxidized hyaluronate. In the present invention, in the obtained amino alcohol grafted modified oxidized hyaluronate, the molar ratio of the grafted amino alcohol to the repeating unit in the oxidized hyaluronate is preferably 1:(2-30).
[0095] In one embodiment, 4-amino-1-butanol and oxidized sodium hyaluronate (OHA) are reacted to prepare 4-amino-1-butanol grafted modified oxidized sodium hyaluronate (abbreviated as OHA-OH), and the reaction scheme is as follows:
[0096]
[0097] In the present invention, the grafting rate of amino alcohol in the amino alcohol-modified oxidized hyaluronate is preferably 9% to 62%.
[0098] [About buffer solution]:
[0099] In the present invention, the buffer solution is preferably PBS buffer. The present invention has no particular limitation on the source of the buffer solution, and any commercial product may be used.
[0100] [About calcium ion donor]:
[0101] In the present invention, the calcium ion donor is preferably an inorganic salt containing calcium, more preferably at least one of calcium sulfate, calcium chloride and calcium lactate, and most preferably calcium chloride. The present invention has no particular limitation on the source of the calcium ion donor, and any commercial product can be used.
[0102] [About material mixing]:
[0103] In the present invention, when the amino alcohol grafted modified oxidized hyaluronate, the buffer solution and the calcium ion donor are mixed, it is preferred to first mix the amino alcohol grafted modified oxidized hyaluronate with the buffer solution to obtain the amino alcohol grafted modified oxidized hyaluronate solution, and then add the calcium ion donor, mix evenly, and obtain the first solution. Among them, the method of adding the calcium ion donor for mixing is preferably ultrasonic treatment; the power of the ultrasonic treatment is preferably 80 to 100 W, specifically 80 W, 85 W, 90 W, 95 W, 100 W; the time of the ultrasonic treatment is preferably 30 to 50 min, specifically 30 min, 35 min, 40 min, 45 min, 50 min. After ultrasonic treatment, a first solution mixed evenly is obtained.
[0104] In the present invention, the concentration of the amino alcohol grafted modified oxidized hyaluronate in the first solution is preferably 2wt% to 6wt%, specifically 2wt%, 3wt%, 4wt%, 5wt%, 6wt%. The concentration of the calcium ion donor in the first solution is preferably 1.0wt% to 1.4wt%, specifically 1.0wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%.
[0105] About step B) :
[0106] B): The hydrazide graft-modified gelatin, the buffer solution and the polyphosphate solution are mixed to obtain a second solution.
[0107] [About hydrazide grafted gelatin]:
[0108] In the present invention, the hydrazide grafted modified gelatin is a grafted modified product obtained by grafting gelatin with hydrazide (ie, introducing hydrazide side groups into the gelatin molecular chain).
[0109] About hydrazide:
[0110] In the present invention, the hydrazide is preferably adipic acid dihydrazide. The present invention has no particular limitation on the source of the hydrazide, and it can be a commercial product.
[0111] About Gelatin:
[0112] Gelatin is a natural high molecular compound, which is hydrolyzed from collagen from animal skulls, skin, muscles, etc., and is widely used in the food industry and the pharmaceutical industry. In the present invention, the gelatin is preferably type A gelatin, specifically type A gelatin derived from Anage product, which is derived from pig skin.
[0113] Regarding the grafting modification of gelatin by hydrazide:
[0114] In the present invention, preferably, the hydrazide grafted modified gelatin is prepared by the following preparation method:
[0115] K1: dissolving gelatin in a solvent to obtain a gelatin solution;
[0116] K2: The gelatin solution is mixed with hydrazide, heated to dissolve, and then an activator is added to react to form hydrazide grafted modified gelatin.
[0117] Regarding step K1:
[0118] The solvent is preferably at least one of PBS solution, MES solution and water; wherein the water is preferably deionized water. The dissolution temperature of gelatin in the solvent is preferably 45-65°C, specifically 45°C, 50°C, 55°C, 60°C, 65°C. The mass fraction of gelatin in the obtained gelatin solution is preferably 1wt%-3wt%, specifically 1wt%, 2wt%, 3wt%.
[0119] Regarding step K2:
[0120] Step K2 preferably specifically includes: K2a: mixing the gelatin solution with hydrazide, heating and dissolving to obtain a mixed solution; K2b: adding an activator to the mixed solution for reaction, maintaining the pH value at 5.0-6.5 during the reaction, and obtaining a reaction solution after the reaction is completed; K2c: dialyzing the reaction solution, freeze-drying, and obtaining hydrazide-grafted gelatin.
[0121] Wherein, the ratio of the molar number of repeating units in the gelatin to the molar number of hydrazide is preferably 1: (30-35), specifically 1: 30, 1: 31, 1: 32, 1: 33, 1: 34, 1: 35. The temperature of heating and dissolving is preferably 45-65°C, specifically 45°C, 50°C, 55°C, 60°C, 65°C. In actual operation, gelatin and solvent are mixed and heated to dissolve to obtain a gelatin solution in step K1, and then maintained at the same temperature, hydrazide is continuously added for mixed dissolution to obtain a mixed solution. The activator is preferably EDCI and NHS. Wherein, the molar ratio of EDCI to NHS is preferably 1: (1.0-1.5), specifically 1: 1.0, 1: 1.1, 1: 1.2, 1: 1.3, 1: 1.4, 1: 1.5. The activator is preferably added in the form of a solution, that is, the activator is dissolved in a solvent in advance to form an activator solution, and then the activator solution is added to the system. The solvent is preferably DMSO and water; wherein the volume ratio of DMSO to water is preferably 1:1. The mass fraction of the activator solution is preferably 8wt% to 16wt%, specifically 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%. The ratio of the number of moles of repeating units in the gelatin to the number of moles of the activator is preferably 1: (2 to 3), specifically 1: 2, 1: 2.5, 1: 3. The temperature of the reaction is not particularly limited and can be carried out at room temperature. The reaction time is preferably 8 to 12h, specifically 8h, 9h, 10h, 11h, 12h. During the reaction, the pH value is maintained at 5.0-6.5, and the maintenance method is preferably as follows: after adding the activator, add acid solution to adjust the pH value to 5.0-6.5, and continue to add acid solution during the reaction to maintain the pH value; preferably, the pH value is adjusted once every 2 hours, and preferably the pH value is maintained for more than 4 hours. The pH value can be specifically 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, 6.0, 6.1, 6.2, 6.3, 6.4, 6.5. The acid solution is preferably HCl solution. After the reaction at room temperature is completed, hydrazide-grafted gelatin is generated in the system, and a reaction solution containing hydrazide-grafted gelatin is obtained. The above reaction solution is dialyzed; specifically, the reaction solution is transferred to a dialysis bag and dialyzed in deionized water. The cutoff of the dialysis bag used for the dialysis is preferably 3.5-7 kDa, specifically 3.5 kDa, 4 kDa, 5 kDa, 6 kDa, and 7 kDa. The dialysis time is preferably 5-7 days, specifically 5 days, 6 days, and 7 days. During the dialysis, the dialysate is preferably replaced every 8-16 hours, specifically 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, and 16 hours. After the dialysis, the solution in the dialysis bag is freeze-dried to obtain hydrazide-grafted gelatin.
[0122] In one embodiment, adipic acid dihydrazide (ADH) and type A gelatin (Gel) are reacted to prepare adipic acid dihydrazide grafted modified gelatin (abbreviated as Gel-ADH), and the reaction route is as follows. Among them, the structural formula on the left is only the structural formula of type A gelatin of Anaiji product, which indicates that the grafted modified group is the amino group on the side chain of gelatin.
[0123]
[0124] In the present invention, the grafting rate of hydrazide in the hydrazide grafted modified gelatin is preferably 37% to 65%.
[0125] [About buffer solution]:
[0126] In the present invention, the buffer solution is preferably PBS buffer. The present invention has no particular limitation on the source of the buffer solution, and any commercial product may be used.
[0127] [About polyphosphate solution]:
[0128] In the present invention, the polyphosphate solution is a solution formed by dissolving polyphosphate in a solvent. The solvent is preferably a PBS solution, an MES solution or water; the water is preferably deionized water. The polyphosphate solution is preferably a sodium polyphosphate solution, more preferably at least one of a sodium hexametaphosphate solution and a sodium tripolyphosphate solution. In the present invention, the concentration of the polyphosphate solution is preferably 0.1 to 0.3 mol / L, specifically 0.1 mol / L, 0.2 mol / L, 0.3 mol / L.
[0129] [About material mixing]:
[0130] In the present invention, when mixing the hydrazide-grafted gelatin, the buffer solution and the polyphosphate solution, it is preferred to first mix the hydrazide-grafted gelatin with the buffer solution to obtain the hydrazide-grafted gelatin solution, and then add the polyphosphate solution and mix evenly to obtain the second solution.
[0131] In the present invention, the concentration of the hydrazide grafted modified gelatin in the obtained second solution is preferably 5wt% to 15wt%, specifically 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%. The concentration of the polyphosphate in the obtained second solution is preferably 0.6wt% to 1.0wt%, specifically 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0wt%.
[0132] About step C) :
[0133] C): mixing the first solution and the second solution to react to obtain a hydrogel; then, freezing the mixture to obtain a hemostatic sponge.
[0134] In the present invention, the mass ratio of the first solution to the second solution is preferably 1:(1.0-1.5), specifically 1:1.0, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, and more preferably 1:1.1.
[0135] In the present invention, the temperature conditions for mixing the first solution and the second solution are not particularly limited, and can be carried out at room temperature; the two solutions are mixed to undergo a Schiff base reaction to form a hydrogel, and at the same time, polyphosphates are complexed with calcium ions to form polyphosphate calcium particles in situ in the hydrogel network. After obtaining the hydrogel, low-temperature freezing is performed to obtain a hemostatic sponge. The freezing temperature is preferably -20 to -60°C, specifically -20°C, -25°C, -30°C, -35°C, -40°C, -45°C, -50°C, -55°C, -60°C, and more preferably -20°C. The freezing time is preferably 12 to 36h, specifically 12h, 24h, 36h, and more preferably 24h. After the above-mentioned low-temperature freezing, it is continued to be freeze-dried, and the freeze-dried time is preferably 36 to 84h, specifically 36h, 48h, 60h, 72h, 84h, and more preferably 72h. After freeze-drying, a hemostatic sponge is obtained.
[0136] In the above-mentioned preparation method provided by the present invention, the hyaluronate therein can be replaced by a polysaccharide of the same type, such as alginate, sodium carboxymethyl cellulose or chondroitin sulfate.
[0137] In the above preparation method provided by the present invention, the gelatin therein can be replaced by other collagen hydrolysate or polymer, specifically polyglutamic acid or polylysine.
[0138] In one embodiment of the present invention, the amino alcohol is 4-amino-1-butanol, the oxidized hyaluronate is oxidized sodium hyaluronate, the calcium ion donor is calcium chloride powder, the hydrazide is adipic acid dihydrazide, the gelatin structure is as shown in the above reaction route, and the polyphosphate solution is sodium hexametaphosphate solution. Calcium chloride powder is dissolved in the oxidized sodium hyaluronate solution grafted and modified by 4-amino-1-butanol as a calcium ion donor to obtain a first solution, and the sodium hexametaphosphate solution is added to the gelatin solution grafted and modified by adipic acid dihydrazide to obtain a hydrogel second solution; the first solution and the second solution are uniformly mixed to undergo a Schiff base reaction to obtain a hydrogel loaded with in-situ formed calcium hexametaphosphate particles, and then the hydrogel is subjected to a low-temperature cryogel technique to obtain the desired hemostatic sponge.
[0139] The present invention also provides a nasal hemostatic sponge prepared by the preparation method described in the above technical solution. The nasal hemostatic sponge obtained by the present invention is a multi-crosslinked nasal hemostatic sponge with strong hemostatic ability and biocompatibility.
[0140] Compared with the prior art, the preparation method of the multi-crosslinked nasal hemostatic sponge with strong hemostatic ability and biocompatibility of the present invention uses a hydrophilic polymer with an aldehyde functional group obtained by an oxidation reaction as a raw material, and then grafts amino alcohol by carbodiimide reaction through activated carboxyl groups, so that the hydrophilic polymer has aldehyde and hydroxyl functional groups, and the amino alcohol grafted modified sodium hyaluronate is used as one of the raw materials for preparing the sponge. A calcium ion donor is dissolved in the amino alcohol grafted modified sodium hyaluronate solution to obtain a first hydrogel solution, and a hydrophilic polymer containing a hydrazide bond or modified by hydrazide grafting is used as another raw material for preparing the hydrogel, and a polyphosphate solution is added to a hydrazide grafted modified gelatin solution to obtain a second hydrogel solution; the first solution and the second solution are uniformly mixed to undergo a Schiff base reaction to obtain a hydrogel loaded with in situ formed polycalcium phosphate particles, and then the hydrogel is subjected to a low-temperature freezing gel technology to obtain the desired hemostatic sponge.
[0141] The present invention performs an oxidation reaction on the polysaccharide hyaluronic acid, introduces an aldehyde group as a functional group, and then performs a graft modification of an amino alcohol small molecule, wherein the amino alcohol small molecule structure is a long alkyl chain skeleton, and the two ends are respectively an amino group and a hydroxyl group. The introduction of the long carbon chain can quickly remove the hydration layer formed by water molecules on the tissue surface through a drainage mechanism when the hemostatic sponge contacts a wet environment, thereby playing a strong wet adhesion effect. When the terminal hydroxyl group forms a hydrogel, it forms a hydrogen bond with the polymer chain inside. In addition, the hydroxyl group can also form a hydrogen bond force with the free group on the tissue surface, and the adhesion strength is further improved, thereby achieving the effect of sealing and stopping bleeding inside the nasal cavity.
[0142] The sponge obtained by the present invention has the structural characteristics of three-dimensional mesh porous, similar to the extracellular matrix, strong water absorption capacity, can absorb exudate at the wound, and has wet adhesion performance, wide raw material sources, low price, good natural polysaccharide biocompatibility, excellent sponge hemostasis effect, and can meet the repair needs of tissue wounds. Wherein, hyaluronic acid and gelatin, two natural high molecular polymers, are grafted and modified respectively, dissolved in a solvent to form a uniform solution, and polyphosphate and calcium ion donor are introduced at the same time. Polyphosphate is a substance contained in the dense granules of platelets, which is a secretion after platelet activation, has the function of triggering the endogenous coagulation pathway, and can also regulate the coagulation process of downstream, and is a powerful coagulant. Calcium ions, as a catalyst, can accelerate the conversion of prothrombin to thrombin, thrombin aggregates fibrin, forms thrombus, and calcium ions promote the interaction between proteins by binding to proteins such as prothrombin and thrombin, thereby accelerating the coagulation process. In addition, calcium ions can also promote the aggregation of platelets and increase the stability of thrombosis. While the gel is forming, the two components form calcium polyphosphate precipitation in situ inside the hydrogel, which not only gives the sponge hemostatic ability but also further enhances its mechanical properties.
[0143] Compared with the prior art, the present invention has the following beneficial effects:
[0144] (1) The multi-crosslinked nasal hemostatic sponge provided by the present invention has strong hemostatic ability and biocompatibility, and the raw materials are all natural polymers with good biocompatibility.
[0145] (2) The multi-crosslinked nasal hemostatic sponge provided by the present invention has strong hemostatic ability and biocompatibility. One of the raw materials, oxidized sodium hyaluronate, is grafted with hydroxyl groups, which enhances the wet adhesion ability of the hemostatic sponge to the nasal bleeding site by enhancing the hydrogen bonding effect with the tissue group.
[0146] (3) The multi-crosslinked nasal hemostatic sponge provided by the present invention has strong hemostatic ability and biocompatibility, and the in situ formed calcium hexametaphosphate particles enhance the hemostatic performance and further enhance the mechanical properties of the hemostatic sponge.
[0147] The test results show that the hemostatic sponge prepared by the present invention achieves the following effects: the hemolysis rate is below 0.4%, showing excellent blood compatibility; it has a rich porous structure and a high cross-linking density. The rich porous structure and the strong covalent bonds and interaction forces make the hemostatic sponge highly elastic and absorbent, and can be filled into the nasal cavity to achieve a rapid hemostatic effect and promote wound healing; the compressive strength after absorbing liquid is above 0.53MPa, and it has excellent strength under stress; the cell survival rate is above 95%, showing excellent cell compatibility; the wet surface firmness reaches above 4.9KPa, showing excellent wet environment adhesion; the liver bleeding repair test shows that it can effectively improve the hemostatic healing ability.
[0148] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.
[0149] Preparatory Example 1: Preparation of graft-modified oxidized sodium hyaluronate (OHA-OH)
[0150] 1. Preparation of oxidized sodium hyaluronate
[0151] The reaction route is as follows:
[0152]
[0153] The process is as follows:
[0154] H1: Weigh 2 g of sodium hyaluronate (HA) into a 250 mL beaker, add 200 mL of deionized water, and stir to dissolve until a colorless, transparent, uniform solution is obtained, i.e., sodium hyaluronate solution.
[0155] H2: Weigh 1.072 g of sodium periodate and dissolve it in 5 mL of deionized water to obtain a sodium periodate solution.
[0156] H3: Slowly add sodium periodate solution to the sodium hyaluronate solution, stir magnetically, and react in the dark at room temperature for 6 hours; then add 1 mL of ethylene glycol to quench the unreacted oxidant and react for 1 hour. The resulting reaction solution is transferred to a 8-1.4 kDa dialysis bag and dialyzed in 2000 mL of deionized water for 3 days, with the dialysate replaced every 8 hours; after dialysis, the solution in the dialysis bag is freeze-dried for 3 days to obtain oxidized sodium hyaluronate solid (OHA).
[0157] 2. Preparation of 4-amino-1-butanol grafted modified oxidized sodium hyaluronate
[0158] The reaction route is as follows:
[0159]
[0160] The process is as follows:
[0161] S1: Weigh 0.5 g (0.0012 mol) of sodium hyaluronate (OHA) into a 200 ml beaker, add 100 ml of deionized water, and stir to dissolve until a colorless, transparent, uniform solution is obtained, i.e., sodium hyaluronate solution.
[0162] S2a: Weigh 0.06 g (0.0006 mol) of 4-amino-1-butanol, add it dropwise into the oxidized sodium hyaluronate solution, stir it evenly with a magnetic stirrer to obtain a mixed solution.
[0163] S2b: Weigh 0.78 g EDCI and 0.77 g NHS and dissolve them in 10 mL solvent (the solvent composition is DMSO:H 2 The activator solution is added to the mixed solution obtained in step S2a, and the pH value is adjusted to 4.5 by adding HCl solution, and the HCl solution is added during the reaction to maintain the pH value for more than 4 hours, and the reaction is carried out at room temperature for 8 hours to obtain a reaction solution.
[0164] S2c: The obtained reaction solution was transferred to a 7 kDa dialysis bag and dialyzed in 2000 mL of deionized water for 3 days, with the dialysate replaced every 8 hours. After dialysis, the solution in the dialysis bag was freeze-dried for 3 days to obtain a solid of oxidized sodium hyaluronate (OHA-OH) grafted with 4-amino-1-butanol.
[0165] Figure 1 FTIR images of sodium hyaluronate before and after being grafted with 4-amino-1-butanol. Figure 2 1HNMR spectra (400 MHz) of sodium hyaluronate before and after being grafted with 4-amino-1-butanol.
[0166] 3. Preparation of other amino alcohol grafted modified oxidized sodium hyaluronate
[0167] The preparation process of item 2 above is followed, except that 4-amino-1-butanol is replaced by 5-amino-1-pentanol, 6-amino-1-hexanol, and 7-amino-1-heptanol in equal molar amounts, thereby obtaining 5-amino-1-pentanol-modified oxidized sodium hyaluronate solid, 6-amino-1-hexanol-modified oxidized sodium hyaluronate solid, and 7-amino-1-heptanol-modified oxidized sodium hyaluronate solid, respectively.
[0168] Preparative Example 2: Preparation of adipic acid dihydrazide grafted gelatin (Gel-ADH)
[0169] The reaction route is as follows:
[0170]
[0171] The process is as follows:
[0172] K1: Weigh 3.0 g of type A gelatin (Gel) into a 500 mL flask, add 300 mL of deionized water, heat to 50°C, and stir magnetically to dissolve to obtain a gelatin solution.
[0173] K2a: While maintaining the heating temperature of step K1, add 2.1 g of adipic acid dihydrazide (ADH) to the gelatin solution and continue stirring until a colorless, transparent, uniform solution is obtained to obtain a mixed solution.
[0174] K2b: Weigh 0.45 g EDCI and 0.77 g NHS and dissolve them in 10 mL solvent (the solvent composition is DMSO:H 2 The activator solution was added to the mixed solution obtained in step K2a, and the pH value was adjusted to 5.5 by adding HCl solution. During the reaction, the HCl solution was added to maintain the pH value for more than 4 hours, and the reaction was carried out at room temperature for 10 hours to obtain a reaction solution.
[0175] K2c: The obtained reaction solution was transferred to a 7 kDa dialysis bag and dialyzed in 2000 mL of deionized water for 7 days, with the dialyzate replaced every 12 hours. After dialysis, the solution in the dialysis bag was freeze-dried for 3 days to obtain adipic acid dihydrazide grafted modified gelatin solid (Gel-ADH).
[0176] Figure 3 FTIR images of gelatin before and after grafting with adipic acid dihydrazide. Figure 4 1HNMR spectra (400 MHz) of gelatin before and after it was grafted with adipic acid dihydrazide.
[0177] Example 1
[0178] A) The oxidized sodium hyaluronate modified by grafting 4-amino-1-butanol obtained in Preparatory Example 1 was dissolved in a PBS buffer solution to obtain a oxidized sodium hyaluronate modified by grafting 4-amino-1-butanol solution; calcium chloride powder was then added, mixed evenly, and sonicated for 30 minutes to obtain a first solution.
[0179] The concentration of oxidized sodium hyaluronate modified by grafting of 4-amino-1-butanol in the obtained first solution was 2 wt %, and the concentration of calcium chloride was 1.0 wt %.
[0180] B) The adipic acid dihydrazide graft-modified gelatin obtained in Preparative Example 2 was dissolved in a PBS buffer solution to obtain an adipic acid dihydrazide graft-modified gelatin solution; an aqueous sodium hexametaphosphate solution (concentration of 0.1 mol / L, added in an amount of 0.1 mL) was then added and mixed uniformly to obtain a second solution.
[0181] The concentration of adipic acid dihydrazide graft-modified gelatin in the obtained second solution was 10 wt %, and the concentration of sodium hexametapolyphosphate was 0.6 wt %.
[0182] C) mixing the first solution and the second solution at a mass ratio of 1:1.1 to form a hydrogel by cross-linking through a Schiff base reaction; and then freeze-drying to obtain a hemostatic sponge.
[0183] Example 2
[0184] A) The oxidized sodium hyaluronate modified by grafting 4-amino-1-butanol obtained in Preparatory Example 1 was dissolved in a PBS buffer solution to obtain a oxidized sodium hyaluronate modified by grafting 4-amino-1-butanol solution; calcium chloride powder was then added, mixed evenly, and sonicated for 40 minutes to obtain a first solution.
[0185] The concentration of the oxidized sodium hyaluronate modified by grafting of 4-amino-1-butanol in the obtained first solution was 4 wt %, and the concentration of calcium chloride was 1.0 wt %.
[0186] B) The adipic acid dihydrazide graft-modified gelatin obtained in Preparative Example 2 was dissolved in a PBS buffer solution to obtain an adipic acid dihydrazide graft-modified gelatin solution; an aqueous sodium hexametaphosphate solution (concentration of 0.1 mol / L, added in an amount of 0.1 mL) was then added and mixed uniformly to obtain a second solution.
[0187] The concentration of the gelatin grafted with adipic acid dihydrazide in the obtained second solution was 12 wt %, and the concentration of the sodium hexametapolyphosphate was 0.6 wt %.
[0188] C) mixing the first solution and the second solution at a mass ratio of 1:1.1 to form a hydrogel by cross-linking through a Schiff base reaction; and then freeze-drying to obtain a hemostatic sponge.
[0189] Example 3
[0190] A) The 4-amino-1-butanol grafted modified sodium hyaluronate obtained in Preparatory Example 1 was dissolved in a PBS buffer solution to obtain a 4-amino-1-butanol grafted modified sodium hyaluronate solution; calcium chloride powder was then added, mixed evenly, and sonicated for 50 minutes to obtain a first solution.
[0191] The concentration of oxidized sodium hyaluronate modified by grafting of 4-amino-1-butanol in the obtained first solution was 6 wt %, and the concentration of calcium chloride was 1.0 wt %.
[0192] B) The adipic acid dihydrazide graft-modified gelatin obtained in Preparative Example 2 was dissolved in a PBS buffer solution to obtain an adipic acid dihydrazide graft-modified gelatin solution; an aqueous sodium hexametaphosphate solution (concentration of 0.1 mol / L, added in an amount of 0.1 mL) was then added and mixed uniformly to obtain a second solution.
[0193] The concentration of the gelatin grafted with adipic acid dihydrazide in the obtained second solution was 14 wt %, and the concentration of the sodium hexametapolyphosphate was 0.6 wt %.
[0194] C) The first solution and the second solution are mixed at a mass ratio of 1:1.1 to form a hydrogel by Schiff base reaction and then freeze-dried to obtain a hemostatic sponge, which is referred to as GO-OH-CaP sponge.
[0195] Example 4
[0196] The method was implemented according to Example 3, except that the oxidized sodium hyaluronate modified by grafting 4-amino-1-butanol was replaced by the oxidized sodium hyaluronate modified by grafting 5-amino-1-pentanol, and the rest was the same as Example 3. The obtained sponge was recorded as GO-OH-1-CaP sponge.
[0197] Example 5
[0198] The method was implemented according to Example 3, except that the oxidized sodium hyaluronate modified by grafting 4-amino-1-butanol was replaced by the oxidized sodium hyaluronate modified by grafting 6-amino-1-hexanol, and the rest was the same as Example 3. The obtained sponge was recorded as GO-OH-2-CaP sponge.
[0199] Example 6
[0200] The method was implemented according to Example 3, except that the oxidized sodium hyaluronate modified by grafting 4-amino-1-butanol was replaced by the oxidized sodium hyaluronate modified by grafting 7-amino-1-heptanol, and the rest was the same as Example 3. The obtained sponge was recorded as GO-OH-3-CaP sponge.
[0201] Comparative Example 1
[0202] The method was implemented according to Example 3, except that the oxidized sodium hyaluronate modified by 4-amino-1-butanol grafting was replaced by unmodified oxidized sodium hyaluronate, and the gelatin modified by adipic acid dihydrazide grafting was replaced by unmodified gelatin, and the rest was the same as Example 3. The obtained sponge was recorded as GO sponge.
[0203] Comparative Example 2
[0204] The method was implemented according to Example 3, except that: in step A), calcium chloride powder was not added when preparing the first solution, and the obtained first solution was a sodium hyaluronate solution grafted and modified by 4-amino-1-butanol, with a concentration of 6 wt %; in step B), sodium hexametapolyphosphate solution was not added when preparing the second solution, and the obtained second solution was a gelatin solution grafted and modified by adipic acid dihydrazide, with a concentration of 14 wt %. The obtained sponge was recorded as GO-OH sponge.
[0205] Comparative Example 3
[0206] Commercial gelatin hemostatic sponge originates from Nanchang Hushida Medical Technology Co., Ltd.
[0207] Product Testing :
[0208] (1) Blood compatibility
[0209] The test method is as follows: dilute the red blood cells in fresh rabbit blood to a 5% red blood cell suspension with normal saline (NS). Then add 1.5 mL of red blood cell suspension to the above-mentioned example and comparative example samples (0.01 g), and incubate at 37°C for 1.5 h, using DI water and NS as positive and negative controls, respectively. After centrifugation at 3000 rpm for 5 min to collect the supernatant, the absorbance at 540 nm was detected. The hemolysis rate was calculated by the formula hemolysis rate = (OD sample - OD negative) / (OD positive - OD negative).
[0210] The above tests were performed on the sponges of Examples 1-6 and Comparative Examples 1-3, respectively. The test results are shown in Table 1. Among them, the test results of the sponges obtained in Example 3 and Comparative Examples 1-2 are as follows: Figure 5 shown.
[0211] Table 1: Hemolysis rate test results of sponge
[0212] Hemolysis rate (%) Example 1 0.36 Example 2 0.27 Example 3 0.19 Example 4 0.20 Example 5 0.18 Example 6 0.19 Comparative Example 1 0.92 Comparative Example 2 0.49 Comparative Example 3 0.79
[0213] It can be seen from the test results in Table 1 that the hemolysis rate of the sponges obtained in Examples 1-3 is below 0.4%, which is significantly lower than that of the comparative example, proving that the hemostatic sponge prepared by the present invention significantly improves blood compatibility.
[0214] (2) Microstructure
[0215] After the sponge surfaces obtained in Example 3 and Comparative Examples 1-2 were sprayed with gold, their structures were observed using a scanning electron microscope. Figure 6 As shown, Figure 6 The SEM images of the sponges obtained in Example 3 and Comparative Examples 1-2 are shown in FIG. Figure 6 (a) is the SEM image of the GO sponge obtained in Comparative Example 1, Figure 6 (b) is the SEM image of the GO-OH sponge obtained in Comparative Example 2. Figure 6 (c) is the SEM image of the GO-OH-CaP sponge obtained in Example 3.
[0216] It can be seen that the GO sponge obtained in Comparative Example 1, the GO-OH sponge obtained in Comparative Example 2, and the GO-OH-CaP sponge obtained in Example 3 all exhibit a rich porous structure, and its structure is attributed to the sublimation of ice crystals in the cross-linked internal of the hydrogel during the freeze-drying process. Among them, the abundant hydroxyl and carboxyl groups in the GO-OH-CaP sponge system obtained in Example 3 can form a large number of hydrogen bonds, making its cross-linking density higher. Not only that, the introduction of amorphous calcium polyphosphate, the electrostatic effect of calcium ions and the carboxyl groups on the polymer side chains, further enhances its cross-linking density. During the freezing process, ice crystals grow and squeeze the dispersion in the solution, leaving a porous structure after freeze-drying. The rich porous structure and strong covalent bonds and interaction forces make the hemostatic sponge highly elastic and absorbent, which can be filled into the nasal cavity to achieve a rapid hemostatic effect and promote wound healing.
[0217] (3) Mechanical properties test
[0218] In the nasal cavity, pressure hemostasis is the main way to stop bleeding, so the nasal packing material needs to have a high compressive strength. More importantly, the foam needs to maintain pressure on the wound after absorbing blood, that is, it needs to be in a moist state. Therefore, the strength of the material under stress is tested.
[0219] The strength test method is as follows: the compression performance of the embodiment and comparative example samples is tested by compressing a cylindrical sponge at a compression rate of 2 mm / min using a universal testing machine. Before testing, the sponge is immersed in deionized water at room temperature for 10 minutes. The stress value when the compression strain reaches 60% is the compressive strength.
[0220] The test results are shown in Table 2.
[0221] Table 2: Mechanical properties test results of sponge
[0222] Compressive strength(MPa) Example 1 0.53 Example 2 0.59 Example 3 0.81 Example 4 0.83 Example 5 0.83 Example 6 0.86 Comparative Example 1 0.39 Comparative Example 2 0.48 Comparative Example 3 0.26
[0223] It can be seen from the test results in Table 2 that the sponges obtained in Examples 1-6 of the present invention have higher strength under stress than those in Comparative Examples 1-3. This is mainly due to the introduction of calcium polyphosphate as a reinforcing substance in the examples; at the same time, a large number of physical cross-linking points greatly enhance the intermolecular forces, so that the material has better strength and toughness under stress; moreover, the pore size of the sponge is reduced, while the porous density is increased, so that the hemostatic sponge has a stronger cross-linking network, and exhibits more excellent mechanical properties in the macroscopic view.
[0224] (4) Cytocompatibility test
[0225] The cytocompatibility of the hemostatic sponge was tested by extraction method. The hemostatic sponge was immersed in DMEM high-glucose medium containing 2 vol% fetal bovine serum and 1 vol% penicillin-streptomycin for 24 h. The concentration of the extract was 0.1 g / mL. The CCK-8 method was used to detect the cytotoxicity of the hemostatic sponge to mouse fibroblasts (L929). The cells were incubated at 1×10 4 The density standard of 10 cells / well was inoculated on a 96-well plate. After culturing for 24 hours, the original culture medium was aspirated and 100 μL of sponge extract was added. The culture was cultured for 1 day. After the extract was removed, 100 μL of DMEM culture medium solution containing 10 vol% CCK-8 was added to each well plate and cultured for 2 hours. After incubation, the absorbance value of the cells at a wavelength of 450 nm was detected, and the cell survival rate was obtained by calculating the absorbance ratio. The test results are as follows: Figure 7 As shown, Figure 7 The cell proliferation diagrams of the sponges obtained in Example 3 and Comparative Examples 1-2 show that the cell survival rate of each sponge is above 95%, indicating that the sponges have good cell compatibility. Figure 8 The cell fluorescence live-dead staining images of the sponges obtained in Example 3 and Comparative Examples 1-2 show that both the examples and comparative examples exhibit good cell compatibility and meet the prerequisites for application in nasal hemostasis and wound repair.
[0226] (5) Adhesion in wet environment
[0227] In order to prevent the hemostatic sponge from falling off from the patient's nasal cavity during use, the sponge's adhesion to the bleeding tissue surface is also important. To this end, the adhesion performance of the grafted modified hemostatic sponge was evaluated.
[0228] The adhesion performance test method is as follows: After collecting the mouse liver, cover the sample on the liver surface and press gently for 10 seconds. Then pick up the sample with tweezers. Use a universal testing machine to further test the adhesion strength of the sponge. First, cut the sponge into 1×1 cm 2 The small pieces were then pressed between the overlapping parts of the two livers with a 20 g weight for 10 min. The shear strength was measured by using a 500 N load at 50 mm min -1 The test results are shown in Table 3.
[0229] Table 3: Wet environment adhesion test results of sponge
[0230] Adhesion strength(KPa) Example 1 4.9 Example 2 6.8 Example 3 8.7 Example 4 8.8 Example 5 8.9 Example 6 8.9 Comparative Example 1 3.5 Comparative Example 2 4.7 Comparative Example 3 1.9
[0231] It can be seen from the test results in Table 3 that the adhesion strength of the sponges obtained in Examples 1-6 of the present invention is above 4.9 KPa, which is significantly higher than that of the comparative example. It can be seen that after the sponges of the examples are grafted with long alkyl chain amino alcohols, due to the hydrophobic effect of the long alkyl chains and the effect of hydroxyl groups on the free groups on the tissue surface, the grafted modified hemostatic sponges show better hemostatic effects and better wet surface firmness in the hemostatic test.
[0232] (6) Liver hemostasis
[0233] The liver of Kunming mice was damaged with a wound of 2 to 3 cm, and the sponge was used to stop bleeding immediately. The hemostatic ability of the hemostatic sponge was determined by weighing the mass of the filter paper before and after hemostasis. A total of four groups of experiments were conducted, namely the blank group, the commercial gelatin sponge group of comparative example 3, the GO sponge group of comparative example 1, the GO-OH sponge group of comparative example 2, and the GO-OH-CaP sponge group of Example 3. The test results are shown in Fig. 9 As shown, Fig. 9 Schematic diagram of the hemorrhage repair of mouse livers obtained by sponges obtained in Example 3 and Comparative Examples 1-2. It can be seen that the GO-OH-CaP sponge group of Example 3 has significantly improved hemostatic healing ability compared to other groups.
[0234] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.
Claims
1. A method for preparing a nasal hemostatic sponge, characterized in that: The following steps are involved: A): mixing the amino alcohol graft-modified oxidized hyaluronate, a buffer solution and a calcium ion donor to obtain a first solution; B): mixing the hydrazide grafted modified gelatin, a buffer solution and a polyphosphate solution to obtain a second solution; C): mixing the first solution and the second solution to react to obtain a hydrogel; Then, freezing is performed to obtain a hemostatic sponge; There is no order restriction for step A) and step B).
2. The preparation method according to claim 1, characterized in that: The amino alcohol grafted modified oxidized hyaluronate is prepared by the following preparation method: S1: dissolving oxidized hyaluronate in a solvent to obtain an oxidized hyaluronate solution; S2: mixing the oxidized hyaluronate solution with amino alcohol and an activator to react to form amino alcohol grafted modified oxidized hyaluronate; The hydrazide grafted modified gelatin is prepared by the following preparation method: K1: dissolving gelatin in a solvent to obtain a gelatin solution; K2: The gelatin solution is mixed with hydrazide, heated to dissolve, and then an activator is added to react to form hydrazide grafted modified gelatin.
3. The preparation method according to claim 1 or 2, characterized in that: The amino alcohol used to form the amino alcohol-grafted modified oxidized hyaluronate is at least one of 4-amino-1-butanol, 5-amino-1-pentanol, 6-amino-1-hexanol and 7-amino-1-heptanol; The oxidized hyaluronate used to form the amino alcohol graft-modified oxidized hyaluronate is an oxidized hyaluronate; wherein the hyaluronate is sodium hyaluronate; The hydrazide grafted modified gelatin is adipic acid dihydrazide grafted modified gelatin; The gelatin used to form the hydrazide grafted modified gelatin is type A gelatin; The calcium ion donor is an inorganic salt containing calcium; The polyphosphate solution is a sodium polyphosphate solution.
4. The preparation method according to claim 3, characterized in that: The calcium ion donor is at least one of calcium sulfate, calcium chloride and calcium lactate; The polyphosphate solution is at least one of a sodium hexametaphosphate solution and a sodium tripolyphosphate solution.
5. The preparation method according to claim 1, characterized in that: The oxidation degree of the amino alcohol graft-modified oxidized hyaluronate is 11% to 86%; The grafting rate of the amino alcohol graft-modified oxidized hyaluronate is 9% to 62%; The grafting rate of the hydrazide grafted modified gelatin is 37% to 65%.
6. The preparation method according to claim 1, characterized in that: The concentration of the amino alcohol grafted modified oxidized hyaluronate in the first solution is 2 wt% to 6 wt%, and the concentration of the calcium ion donor is 1.0 wt% to 1.4 wt%; The concentration of hydrazide grafted modified gelatin in the second solution is 5wt% to 15wt%, and the concentration of polyphosphate is 0.6wt% to 1.0wt%; The concentration of the polyphosphate solution used is 0.1-0.3 mol / L; The mass ratio of the first solution to the second solution is 1:(1-1.5).
7. The preparation method according to claim 1 or 2, characterized in that: The oxidized hyaluronate used to form the amino alcohol graft-modified oxidized hyaluronate is prepared by the following preparation method: hyaluronate reacts with sodium periodate to form oxidized hyaluronate.
8. The preparation method according to claim 7, characterized in that: The preparation method of the oxidized hyaluronate specifically comprises: H1: dissolving hyaluronate in a solvent to obtain a hyaluronate solution; H2: dissolving sodium periodate in a solvent to obtain a sodium periodate solution; H3: adding the sodium periodate solution dropwise to the hyaluronate solution, reacting in the dark to form oxidized hyaluronate; There is no order restriction for step H1 and step H2.
9. The preparation method according to any one of claims 1 to 8, characterized in that Replace the hyaluronate with alginate, sodium carboxymethylcellulose or chondroitin sulfate; and / or The gelatin therein is replaced with other collagen hydrolysates or polymers.
10. A nasal hemostatic sponge, characterized in that: The method is prepared according to any one of claims 1 to 8.
Citation Information
Cited By
Injectable self-expanding liquid foam hemostatic material with coagulating activity and wet adhesion as well as preparation method and application of injectable self-expanding liquid foam hemostatic material
CN121313919A
An injectable self-expanding liquid foam hemostatic material with procoagulant activity and wet adhesion, its preparation method and application.
CN121313919B